A Reciprocal and Dynamic Development Model for the Effects of Siblings on Children’s Theory of Mind - Hou, Xiao-Hui; Gong, Zhu-Qing; Wang, Liu-Ji; Zhou, Yuan; Su, Yanjie (Frontiers in Psychology, 2020)
In the field of social influences on Theory of Mind (ToM), more research has focused on the role of parents, but less research has examined the impact of siblings on children's social understanding. We review existing research related to what factors might affect sibling-ToM association and how these potential factors affect ToM. Based on the literature review, we propose an integrative model that unites three categories of factors (i.e., sibling structural variables, sibling individual variables, parental intervening variables) that might have effects on the sibling-ToM association and highlights mental state talks during sibling interactions at the intersection of sibling-related variables and ToM. Furthermore, we propose some issues arising from this review that need to be clarified in future studies. Specifically, we hope to clarify the specific effects of older and younger siblings on children's understanding of minds, the similarities and differences of sibling-ToM association under different cultural backgrounds, and the impact of social disadvantage on the sibling-ToM association. All these works would benefit from the verification, revision, and expansion of our reciprocal influence model for the sibling-ToM association.